Confronting Biospecimen Exceptionalism in Proposed Revisions to the Common Rule - Lynch, Holly Fernandez (The Hastings Center report, 2016)
On September 8, 2015, the Department of Health and Human Services issued a Notice of Proposed Rule Making to revise the Federal Policy for the Protection of Human Subjects, widely known as the “Common Rule.” The NPRM proposes several changes to the current system, including a dramatic shift in the approach to secondary research using biospecimens and data. Under the current rules, it is relatively easy to use biospecimens and data for secondary research. This approach systematically facilitates secondary research with biospecimens and data, maximizing the capacity for substantial public benefit. However, it has been criticized as insufficiently protective of the privacy and autonomy interests of biospecimen and data sources. Thus, the NPRM proposes a more restrictive regime, although more so for biospecimens than data. Both the status quo and the NPRM's proposal are critically flawed.